Is day case liver biopsy underutilised?. Issue 4 (October 1995) - Douds, A C; Joseph, A E; Finlayson, C; Maxwell, J D
Abstract : Day case liver biopsies are rarely performed nationally but have been routine practice in selected patients in our hospital since 1989. We have audited our experience of this procedure to compare its safety, and efficacy with inpatient biopsy and assess patient acceptability. Audit data were collected retrospectively on liver biopsies performed at a teaching hospital over 42 months. Acceptability of day case biopsy was assessed by a questionnaire. A total of 182 of 546 biopsies were day cases (33%). The specimen quality was similar in both groups. The overall complication rate did not significantly differ between the two groups (2.7% day case v 3.3% inpatients). There were no deaths or episodes of haemorrhage in the day cases but one patient developed a pneumothorax. Some 91% of those who had a day case biopsy were satisfied with the procedure. Day case liver biopsy is safe, effective, and acceptable in selected patients.